Detection of Non-Tuberculous Mycobacteria and Treatment of Mycobacteriosis in Arkhangelsk Oblast in 2010–2020 - P. I. Eliseev; T. I. Gurieva; E. I. Nikishova; E. S. Khimova; A. O. Maryandyshev (Туберкулез и болезни лёгких)
The objective: to assess detection rates of non-tuberculous mycobacteria (NTM), incidence of mycobacteriosis, and results of mycobacteriosis treatment in Arkhangelsk Oblast from 2010 to 2020.Subjects and Methods. All patients in whom mycobacteria were detected by microscopy and/or culture with a negative result for M. tuberculosis were examined for NTM. Patients with NTM who had two positive cultures and/or clinical findings suggestive of the disease received treatment of mycobacteriosis.Results. In Arkhangelsk Oblast from 2010 to 2020, NTM were detected in 138 people, with an average rate of 1.09 cases per 100,000 population. Mycobacteria belonging to the M. avium complex (M. avium and M. intralcelulare) (MAC) were reported in the majority of cases (56/138; 40%). In 19/138 (14%) patients, the type of NTM could not be determined. The diagnosis of mycobacteriosis was registered in 67/138 (49%) people, with an average rate of 0.53 cases per 100,000 population. In 45/67 (67%) cases, the disease was caused by MAC. In 71/138 (51%) patients with NTM, no mycobacteriosis was diagnosed. Treatment was started in 60/67 (90%) patients with mycobacteriosis, and in 58/60 (97%) the regimen contained clarithromycin. Results were as follows: treatment was completed in 37 (62%) patients, 10 (16%) patients were defaulters, treatment was canceled for medical reasons in 5 (8%) cases, 1 (2%) patient died of mycobacteriosis, 4 (7%) patients died of other causes, 2 (3%) patients were transferred out, and treatment failed in 1 (2%) patient.